Contribution of the ACE (rs1799752) and CYP11B2 (rs1799998) Gene Polymorphisms to Atrial Fibrillation in the Tunisian Population. Issue 1 (January 2022) - Gouissem, Ilhem; Midani, Fatma; Soualmia, Hayet; Bouchemi, Meryem; Ouali, Sana; Kallele, Ameni; Romdhane, Neila Ben; Mourali, Mohamed Sami; Feki, Moncef
Background: This study investigated the association of angiotensin–converting enzyme (ACE I/D) and aldosterone synthase (CYP11B2-344C/T) gene polymorphisms in the renin–angiotensin–aldosterone system (RAAS) with atrial fibrillation (AF) in the Tunisian population. Materials and Methods: The study population included 120 patients with AF and 123 age-matched controls. Genotyping of the I/D polymorphism in the ACE gene and the -344C/T polymorphism in the CYP11B2 gene was performed by polymerase chain reaction (PCR) and PCR-RFLP methods, respectively. Results: The genotype distribution of the ACE I/D and CYP11B2-344C/T polymorphisms was significantly different between AF patients and control participants ( p < 0.01 and p < 0.006 respectively). In addition, ACE I/D increased the risk of AF significantly by 3.41-fold for the DD genotype (OR = 3.41; 95% CI [1.39–8.34]; p < 0.007), and after adjusting for confounding factors (age, diabetes, hypertension, and dyslipidemia), the risk was higher (OR = 5.71; 95% CI [1.48–21.98]; p < 0.01). Likewise, the CYP11B2-344C/T polymorphism increased the incidence of AF for the TT genotype (OR = 3.66; 95% CI [1.62–8.27]; p < 0.002) and the CT genotype (OR = 2.68; 95% CI [1.22–5.86]; p < 0.01). After adjusting for confounding factors (age, diabetes, hypertension and dyslipidemia), the risk remained higher for the TT genotype (OR = 3.58; 95% CI [1.08–11.77]; p < 0.03). Furthermore, the haplotype–based association of the ACE I/D and CYP11B2-344C/T polymorphisms showed that the D-T haplotype increased the risk for AF. Conclusion: Our study suggests a significant association of the ACE (I/D) and CYP11B2-344C/T polymorphisms with AF in the Tunisian population.